2021
DOI: 10.1186/s12889-021-10476-7
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in influenza vaccination: Arab Americans in California

Abstract: Background Influenza vaccination among minoritized groups remains below federal benchmarks in the United States (US). We used data from the 2004–2016 California Health Interview Surveys (CHIS) to characterize influenza vaccination patterns among Arab Americans in California. Methods Influenza vaccination was self-reported by Arab American adults (N = 1163) and non-Hispanic Whites (NHW, N = 166,955). Differences in influenza vaccination prevalence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Other studies in general US populations have found greater vaccine intention in women with regard to both COVID-19 and non-COVID-19 vaccines [28]. Previous work has found that Arab American women have lower vaccination rates and preventive care engagement when compared to non-Arab American women [22,23]. Foreignborn Arab women have been found to have the lowest rates of vaccination in this community [22].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Other studies in general US populations have found greater vaccine intention in women with regard to both COVID-19 and non-COVID-19 vaccines [28]. Previous work has found that Arab American women have lower vaccination rates and preventive care engagement when compared to non-Arab American women [22,23]. Foreignborn Arab women have been found to have the lowest rates of vaccination in this community [22].…”
Section: Discussionmentioning
confidence: 83%
“…Predictor variables were included based on prior work [23,26,27] and were categorized into one of the following groups: sociodemographics, immigration and acculturation related variables, and COVID-19 risk factors. Sociodemographic predictors included age (18-25, 26-34, 35-54, 55 +), region of residence (West, Midwest, South, Northeast), education (high school or less, some college/ associate's degree, college degree, graduate degree), religion (Christianity, Islam, Other), annual household income ($0-5 K, $5-45 K, $46-99 K, > $100 K), health insurance status (yes, no/don't know), and religiosity (extremely/ very important, slightly/moderately important, not at all important).…”
Section: Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several national studies have shown that influenza vaccine uptake, cancer screenings, and other efforts are lower among Arab Americans compared to other groups [ 4 , 5 , 28 ]. Coupled with the findings of the current study and that vaccine hesitancy is a concern in the Arab American community [ 29 ], there is a need for targeted prevention intervention programs about the risks of COVID-19 among Arab Americans.…”
Section: Discussionmentioning
confidence: 67%
“…For example Arab Americans in California were 10% less likely to receive the influenza vaccine in comparison to whites, yet there were no appreciable differences after adjusting for health behaviors, sociodemographic variables and acculturation status. 20 National level data indicate that some Asian American subgroups such as Asian Indians and select other Asian groups may actually have higher influenza vaccination rates in comparison to Whites in some instances. 21 Collectively the data indicates that Blacks and Hispanics are the most vulnerable racial and ethnic subgroups with regards to influenza and pneumococcal related vaccine disparities.…”
Section: Introductionmentioning
confidence: 99%